REGISTRO DE UN MERO NEGRO ADULTO, HYPORTHODUS NIGRITUS (PERCIFORMES: EPHINEPHELIDAE), EN UN ARRECIFE PROFUNDO DEL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
The Warsaw grouper (Hyporthodus nigritus) has been reported from the western Atlantic between Massachusetts (United States) and Mexico, including a few South American reports to Brasil. In Colombia a juvenile specimen was reported from nearby Cartagena in 2003. Herein, we report an adult fih caught near to deep-water reefs in the Golfo de Morrosquillo, Colombian Caribbean.